Aqueous two-phase systems in Latin America: perspective and future trends - González-González, Mirna; Picó, Guillermo; Lima, Álvaro Silva; Ussemane Mussagy, Cassamo [UNESP]; Pereira, Jorge Fernando Brandão [UNESP]; Fernandez-Lahore, Hector Marcelo; Asenjo, Juan A.; Rito-Palomares, Marco (Wiley, 2021)
Aqueous two-phase systems (ATPS) have been demonstrated to be a simple and robust worldwide applied bioprocessing technology. From high value microscopic to macroscopic biological molecules obtained from a wide broad of matrices, ATPS have shown a high efficiency capacity for their concentration, enrichment, recovery, and purification. Particularly in Latin America, four relevant countries have paved the way and played important leading roles in this transformation history. This perspective article aims to present a critical analysis of the practical evolution of the main implementations of ATPS in Argentina, Brazil, Chile, and Mexico. Special attention is given to novel applications of this biphasic bioprocess that are being explored to accomplish visionary therapeutic tasks for the healthcare, biotechnology, and pharmaceutical sectors, as well as other environmental purposes. © 2021 Society of Chemical Industry (SCI).
Keywords: applications; ATPS; bioprocess; trends